Late onset of biliobronchial fistula — a serious complication of hemihepatectomy for atrophic liver with hepatolithiasis: a case report and review of the literature - Chen-Ze Yan; Zhong Jia; Ya-Feng Wan; He-Shan Zhou (Journal of Cardiothoracic Surgery)
Abstract Background Acquired bronchobiliary fistula (BBF) is a rare but life-threatening complication that can occur as a result of oncological processes, inflammatory reactions, parasite infections, thoracoabdominal trauma, or invasive procedures associated with iatrogenic injury. However, the potential etiology of BBF caused by instrumental issues when using ultrasonic scalpels resulting in diathermy burn and its post-burn effects has never been reported. Case presentation Herein, we present a case of a 65-year-old woman who developed BBF one month after hepatectomy and presented with refractory irritating cough accompanied by yellow bitter sputum. The diagnosis was confirmed through detection of bile components in the sputum, fiberoptic bronchoscopy examination, and endoscopic retrograde cholangio-pancreatography (ERCP). Unfortunately, both endobronchial blocker and endoscopic nasobiliary drainage (ENBD) failed to address the condition until surgical removal of the involved subdiaphragmatic fistula followed by pedicled greater omentum tamping were performed. After closure of the fistula during a 5-month follow-up period, she did not experience any further episodes of biloptysis. Conclusions For diathermy burn associated BBF, non-surgical management proves difficult due to inadequate or ineffective biliary drainage, so that early surgical intervention should be considered as an effective approach. Moreover, the adhesion between the atrophied liver and the diaphragm may pose a significant risk factor for diathermy burn, necessitating heightened vigilance.